1999
DOI: 10.2165/00007256-199927030-00001
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction and the Long Term Incidence of Gonarthrosis

Abstract: Knee ligament injuries are common in sport. A rupture of the anterior cruciate ligament (ACL) is the most serious of these injuries because it may cause long term disability. In this literature review, the frequency of post-traumatic gonarthrosis is examined. There are few long term prospective studies but a number of retrospective studies with follow-up times between 5 and 20 years have been published. These studies show that radiographic gonarthrosis is significantly increased after all knee injuries compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
212
1
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(231 citation statements)
references
References 97 publications
8
212
1
7
Order By: Relevance
“…However, we found no correlation between instability and OA. Similar conclusions were reached by Sommerlath et al [3] and Gillquist and Messner [2].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…However, we found no correlation between instability and OA. Similar conclusions were reached by Sommerlath et al [3] and Gillquist and Messner [2].…”
supporting
confidence: 85%
“…However, we found no correlation between instability and OA. Similar conclusions were reached by Sommerlath et al [3] and Gillquist and Messner [2].Roe et al [4] reported that ACL reconstruction patients with PT autograft showed higher OA incidence than those with hamstring autograft. However in our study we used a patellar tendon autograft in all cases and we have provided no information about the relationship between OA and graf t choice (PT or hamstring).…”
supporting
confidence: 71%
“…Because there is little potential for spontaneous recovery of the ACL following complete rupture (18) and OA frequently develops in these individuals, surgical intervention would appear logical to maintain knee joint stability. Despite this, studies have suggested that surgery may actually hasten the development of OA (4).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the obvious acute injury effects, knee joint musculoskeletal injury often potentiates the likelihood of significant long-term debilitation. It has been shown for example, that ACL injury presents an 8 -10 fold increase in the long-term incidence of osteoarthritis [4,5].…”
Section: Introductionmentioning
confidence: 99%